The Attractiveness of Poland for Economic Migrants. Assessment by Employers: Results of Empirical Studies - Kubiciel-Lodzińska, Sabina; Ruszczak, Bogdan (Olsztyn Economic Journal, 2018)
This paper discusses selected results of studies carried out among employers from the Opolskie Voivodeship: a region with an exceptional scale of labour emigration in Poland that is struggling with an increasingly palpable shortage of workers. The study included 263 employers and was carried out in late 2014 and in early 2015. It involved managers, i.e. owners, directors, managers or people responsible for personnel policy in enterprise. The CAWI and PAPI methods were used. The research used a structured interview schedule. The aim was to show how the enterprises evaluated Poland in respect to its attractiveness to foreign workers and specified the main issues that were decisive to the influx of foreigners taking up employment in Poland. More than 46% of representatives of the enterprises involved in the study claimed that Poland is attractive to foreigners interested in taking up work. Respondents were convinced that the main factor attracting foreign workers to Poland was the relative proximity of their country of origin and the related easy access.